Phosphoric‐Acid Retention in High‐Temperature Proton‐Exchange Membranes. Issue 70 (19th October 2022) - Tang, Hongying; Gao, Jian; Wang, Yidong; Li, Nanwen; Geng, Kang
Abstract: Great efforts have been conducted to develop high temperature proton exchange membrane fuel cell (HT‐PEMFC) due to its features of enhanced electrocatalyst reactivity, simplified hydrothermal management system and high CO tolerance of catalysts, and remarkable progress has been achieved. However, the easy leaching of phosphoric acid (PA) from the membranes during operation limits its commercial scale‐up in complicated environments. This concept here mainly focuses on the recent developments for mitigation of PA loss in PEMs. The probable mechanisms of PA loss are proposed. The approaches to improve PA retention for example via introduction of phosphonic acid by covalent bond, using ion‐pairs interaction and siphoning effect, and blending with inorganic nanoparticles are described in detail. Among these strategies, the siphoning effect from the intrinsic microporous PEMs is the most efficient and enables the cell to operate flexibly within a broad temperature range. Therefore, this concept may provide new ideas for the scientists to retain PA, to improve the cell performance and expand the potential applications of PA doped PEMs at elevated humidity and wide temperature range. Abstract : Strategies to improve PA retention : The leakage of phosphoric acid (PA) from PA‐doped proton‐exchange membranes (PEMs) is a key issue for high‐temperature proton‐exchange membrane fuel cells (HT‐PEMFCs). The detailed discussion of the recent progress to mitigate the PA loss in HT‐PEMs is described in this Concept. Moreover, a new idea is provided on how to decrease the leaching of PA in PEMs with a high acid concentration, and how to address the remaining technical issues.